A Tudor story : the return of Anne Boleyn - Pakenham-Walsh, W. S. (William Sandford), 1868-1960 (Lutterworth Press, 2006)
No-one who knew the late Canon Pakenham-Walsh could accuse him of being a starry-eyed dreamer. At ninety he was as active mentally and physically as many a man little more than half his age. Join him on his personal journey across psychic channels to find the real Anne Boleyn; a journey, which beneath its psychic and historical drama, demonstrates religious purpose. The author's deep-rooted fascination for Anne Boleyn first originated in 1917 during a missionary trip in China, yet it was on his return to England in 1919 that Pakenham-Walsh began to see divine confirmation of his desire to unco.